GAS TURBINE PERFORMANCE ANALYSIS OPERATING WITH LOWHEATING VALUE FUELS - Silva, E. B.; Bringhenti, C.; Assato, M.; Lima, R. C. (Revista de Engenharia Térmica, 2013)
Usually, power plants work with gas turbine designed to fire natural gas; however, there are possibilities to use other types of gaseous fuels with different calorific values that may be available close to the power plant site. These fuels can be gases obtained from steel (from blast furnaces and coking plants), from gasification processes of coal or biomass, among others. In this work, a gas turbine performance was evaluated at different operational conditions in order to verify the technical feasibility of burning low calorific value fuels. A gas turbine designed to operate with natural gas was used as a reference, the model was built and the performance evaluated at design and off-design conditions using a commercial computer program, GasTurb 11®. A good agreement was obtained between the model operating with natural gas and the available data from open literature, at design and off-design conditions. The model was simulated using low heating value fuels under the same conditions established for natural gas. A reduction in compressor’s surge margin was identified when using low heating value fuels as well as an increase in power output. Therefore, for safe operation a strategy for recovering the surge margin was adopted. In this study the control strategy adopted was bleed air at the compressor discharge. This control strategy presents a technical viability and ensures that the gas turbine operates with the same surge margin level as when using natural gas.